Metode TGT (Teams Games Tournament) untuk Meningkatkan Hasil Belajar Matematika - Sukatmi, Sukatmi (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
In general, mathematics is a subject that is considered difficult and disliked by students. Mathematics is difficult to understand, understand and learn, so mathematics lessons become scary, boring and less attractive to students. So that the impression is gradually lost, teachers are required to be willing and able to design and implement learning activities that attract students' interest and attention. In addition to the media, the proper integration of various methods is absolutely necessary. The creativity of teachers is still needed to choose a method that is suitable for the material and conditions encountered, so that mathematics becomes a fun lesson... an effort to improve student learning outcomes by using the TGT (Teams Games Tournament) learning model. The TGT method was first developed by David De Vries and Keith Erdward. The TGT method is the first learning method from John Hopkins. (Slavin, 2008 :13). This method is an approach to cooperation between groups by developing interpersonal cooperation. Learning mathematics using the games method will be more fun for children.